The effect of patient institutional transfer during the interstage period of two-stage treatment for prosthetic knee infection. (September 2019) - Garceau, Simon; Warschawski, Yaniv; Dahduli, Omar; Alshaygy, Ibrahim; Wolfstadt, Jesse; Backstein, David
Abstract : Aims: The aim of this study was to assess the effects of transferring patients to a specialized arthroplasty centre between the first and second stages (interstage) of prosthetic joint infection (PJI) of the knee. Patients and Methods: A search of our institutional database was performed to identify patients having undergone two-stage revision total knee arthroplasty (TKA) for PJI. Two cohorts were created: continuous care (CC) and transferred care (TC). Baseline characteristics and outcomes were collected and compared between cohorts. Results: A total of 137 patients were identified: 105 in the CC cohort (56 men, 49 women; mean age 67.9) and 32 in the TC cohort (17 men, 15 women; mean age 67.8 years). PJI organism virulence was greater in the CC cohort (36.2% vs 15.6%; p = 0.030). TC patients had a higher rate of persisting or recurrent infection (53.6% vs 13.4%; p < 0.001), soft-tissue complications (31.3 vs 14.3%; p = 0.030), and reduced requirement for porous metal augments (78.1% vs 94.3%; p = 0.006). Repeat first stage debridement after transfer led to greater need for plastic surgical procedures (58.3% vs 0.0%; p < 0.001). Conclusion: Patient transfer during the interstage of treatment for infected TKA leads to poorer outcomes compared with patients receiving all their treatment at a specialized arthroplasty centre. Cite this article: Bone Joint J 2019;101-B:1087–1092.